Pemikiran M. Syahrur Tentang Pakaian Perempuan (Dari Konfigurasi Aurat Hingga Konstruk-Hirarki Pakaian Perempuan Dalam Islam) - Wendi Parwanto (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2021)
Muhammad Syahrur's thoughts in several disciplines of discussion are quite interesting for researchers to discuss, both in the fields of hadith, interpretation, fiqh and al-Qur'an hermeneutics. The main theory that is of great interest to researchers in Syahrur's thinking is the limit theory. And it is from this limit theory that Syahrur constructs his thoughts on many Islamic themes, including women's clothing, genitalia and so on. So in this study, we will examine in more detail about the construction of aurat and women's clothing according to Muhammad Syahrur. This research is a library research with the main sources are two literatures by M. Syahrur, namely: Al-Kitabu wa Al-Qur`anu and Nahwa Al-Jadidah li Al-Fiqh Al-Islamiy. While the secondary sources are other relevant literature. The conclusion of this article is that the construction of Muhammad Syahrur's thoughts on genitalia, headscarves, zinah (jewelry), and all women's clothing comes from the limit theory (hudud). According to him, the upper and lower limits depend on the extent to which a person is ashamed. However, not all of his thoughts tend to contradict the majority of Muslim scholars, because before he concluded the limit theory (hudud), he also explained about the derivation of words, such as headscarves, khimar, and others.